The meso-octoploid Heliophila variabilis genome sheds a new light on the impact of polyploidization and diploidization on the diversity of the Cape flora - Huang, Yile; Guo, Xinyi; Zhang, Kang; Mandáková, Terezie; Cheng, Feng; Lysak, Martin A (The Plant journal, 2023)
Although the South African Cape flora is one of the most remarkable biodiversity hotspots, its high diversity has not been associated with polyploidy. Here, we report the chromosome-scale genome assembly of an ephemeral cruciferous species Heliophila variabilis (~334 Mb, n = 11) adapted to South African semiarid biomes. Two pairs of differently fractionated subgenomes suggest an allo-octoploid origin of the genome at least 12 million years ago. The ancestral octoploid Heliophila genome (2n = 8x = ~60) has probably originated through hybridization between two allotetraploids (2n = 4x = ~30) formed by distant, intertribal, hybridization. Rediploidization of the ancestral genome was marked by extensive reorganization of parental subgenomes, genome downsizing, and speciation events in the genus Heliophila. We found evidence for loss-of-function changes in genes associated with leaf development and early flowering, and over-retention and sub/neofunctionalization of genes involved in pathogen response and chemical defense. The genomic resources of H. variabilis will help elucidate the role of polyploidization and genome diploidization in plant adaptation to hot arid environments and origin of the Cape flora. The sequenced H. variabilis represents the first chromosome-scale genome assembly of a meso-octoploid representative of the mustard family.
Keywords: rostliny; Plants; polyploidie; southern Africa; genome diploidization; whole-genome duplication; biodiverzita; Polyploidy; chromosomal rearrangements; octoploidy; polyploidy; Brassicaceae; genom rostlinný; genome assembly; Genome, Plant; Biodiversity; adaptive evolution